Pengaruh Gaya Kepemimpinan dan Komitmen Organisasi terhadap Kinerja Karyawan Non Medis RS. Cut Nyak Dhien Langsa - Teguh Suharto; Yuniati Yuniati; Ria Kesumawati (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Performance is the result of the work of individuals in carrying out the responsibilities given, which is greatly influenced by the factors of ability, experience, seriousness, and punctuality. Data from Cut Nyak Dhien Hospital shows a decrease in the performance of non-medical employees recorded by the personnel department every year. In 2019, the average employee performance was 87.8; However, the figure decreased to 86.2 in 2020, 85.5 in 2021, 84.0 in 2022, and 83.9 in 2023. This decline is suspected to be caused by a less effective leadership style and weak implementation of organizational commitments. This study aims to analyze the influence of leadership style and organizational commitment on the performance of non-medical employees at Cut Nyak Dhien Langsa Hospital in 2024. The method used is a descriptive quantitative approach with a cross-sectional research design. The population studied was 35 non-medical employees, all of whom were sampled. Data were analyzed using univariate, bivariate, and multivariate tests. The results showed that the majority of respondents assessed the leadership style at the hospital as not good (57.1%), low organizational commitment (60.0%), and poor performance (57.1%). Statistical tests showed that there was a significant influence between leadership style (p=0.001) and organizational commitment (p=0.002) on the performance of non-medical employees. Based on these findings, it is recommended that Cut Nyak Dhien Langsa Hospital implement a more democratic leadership style to improve the performance of non-medical employees. Additionally, it is important to strengthen the implementation of the organization's commitments by providing ongoing training and development, as well as creating a work environment that supports employees' active participation in decision-making. The implementation of policies based on collaboration and good communication between management and employees is expected to be able to create a more productive and harmonious work atmosphere, which is important to achieve organizational goals effectively.